Needs and Wishes Towards Sex- and Gender-Sensitive Chronic Pain Management: A Qualitative Study with German General Practitioners - Piotrowski A; Schmidt A; Seuken N; Goldberg L; Kufeld N; Kersting C; Bencheva V; Thürmann P; Mortsiefer A (Journal of Pain Research, 2025)
Alexandra Piotrowski,1 Alexandra Schmidt,1 Natalie Seuken,1 Lia Goldberg,1 Neele Kufeld,2 Christine Kersting,1 Veronika Bencheva,3 Petra Thürmann,3,4 Achim Mortsiefer1 On behalf of the GESCO study group1General Practice II and Patient-Centeredness in Primary Care, Institute of General Practice and Primary Care, Faculty of Health, Witten/Herdecke University, Witten, Germany; 2General Practice I and Interprofessional Care, Institute of General Practice and Primary Care, Faculty of Health, Witten/Herdecke University, Witten, Germany; 3Clinical Pharmacology, Faculty of Health, Witten/Herdecke University, Witten, Germany; 4Philipp Klee-Institute of Clinical Pharmacology, Helios University Hospital Wuppertal, Wuppertal, GermanyCorrespondence: Alexandra Piotrowski, Witten/Herdecke University, Faculty of Health, Alfred-Herrhausen-Str. 50, Witten, 58448, Germany, Email Alexandra.piotrowski@uni-wh.dePurpose: This study is part of the GESCO feasibility project (funded by the German Federal Ministry of Health) aimed at developing a sex- and gender-sensitive primary care intervention for patients with chronic non-cancer pain (CNCP) receiving long-term opioid therapy (LTOT). To inform the intervention design, we explored general practitioners’ (GPs) experiences and needs in managing this patient group, with a particular focus on the role of sex and gender.Methods: We conducted semi-structured telephone interviews with five GPs in Germany using a convenience sample. Interviews were transcribed verbatim and analyzed using the Rapid approach to integrate findings quickly into the broader project.Results: Treating patients with CNCP and LTOT is highly complex and emotionally demanding. GPs described feeling caught between patients’ high expectations and their own limitations, which often strained therapeutic relationships. Gender dynamics played a key role in shaping these interactions. While male GPs emphasized neutrality, underlying gender stereotypes still influenced their behavior. Female GPs reported stronger trust with female patients, while male GPs described a greater focus on asserting control. Stigmatization—especially affecting female patients—was reported to hinder open communication and trust. GPs expressed the need for more time, better training in gender-sensitive care, and stronger interdisciplinary collaboration.Conclusion: To improve care for patients with CNCP and LTOT, recommendations include: extending consultation times with adequate reimbursement, ensuring comprehensive medical histories, enhancing GP training in gender-sensitive care, improving diagnostic tools, and promoting peer collaboration. Further measures involve supporting patient self-management, empathy, and communication, as well as adopting a biopsychosocial and sex- and gender-sensitive approach to treatment.Keywords: long-term opioid therapy, chronic non-cancer pain, chronic pain in general practice, sex- and gender-sensitive medical care, needs assessment